2016
DOI: 10.1038/ncomms10802
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the interfacial structure of nanomaterials to achieve a unique combination of strength and ductility

Abstract: The control of interfaces in engineered nanostructured materials has met limited success compared with that which has evolved in natural materials, where hierarchical structures with distinct interfacial states are often found. Such interface control could mitigate common limitations of engineering nanomaterials. For example, nanostructured metals exhibit extremely high strength, but this benefit comes at the expense of other important properties like ductility. Here, we report a technique for combining nanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(151 citation statements)
references
References 53 publications
11
130
0
2
Order By: Relevance
“…Grain boundaries (GBs) are ubiquitous structural defects in polycrystalline materials governing mechanical, functional and kinetic properties of the film. [1][2][3] Because of the excess of free energy per unit area at the grain boundary region, GBs are detected as the sink of defects including dislocations, voids, impurities, and alloying elements in the multicomponent alloy, and they are observed as the prone route for deformation events including fracture, crack, and corrosion. [4,5] Many properties of pure metals can be improved by mixing the parent element with different elements, forming a multicomponent alloy to take advantage of their synergetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Grain boundaries (GBs) are ubiquitous structural defects in polycrystalline materials governing mechanical, functional and kinetic properties of the film. [1][2][3] Because of the excess of free energy per unit area at the grain boundary region, GBs are detected as the sink of defects including dislocations, voids, impurities, and alloying elements in the multicomponent alloy, and they are observed as the prone route for deformation events including fracture, crack, and corrosion. [4,5] Many properties of pure metals can be improved by mixing the parent element with different elements, forming a multicomponent alloy to take advantage of their synergetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly quenching instead leads to the AIFs accessed at elevated temperatures to be frozen into place, so this specimen will be referred to as the AIF-containing sample. Since AIFs are only thermodynamically preferred at high temperature, it is important to remember that the AIFs quenched into place are therefore only metastable at room temperature [29,56,57]. It is also important to note that AIFs do not exist at every grain boundary because of the heterogeneous distributions of grain boundary energy, structure, and local chemistry [30,56].…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has shown that AIF formation is promoted in alloys that have dopant segregation to the grain boundary and a negative enthalpy of mixing [55]. Cu doped with Zr satisfies these criteria and nanocrystalline Cu-Zr alloys have been shown previously to form AIFs [34,56]. In this study, the impact of AIFs on radiation tolerance is evaluated experimentally by comparing the response of nanocrystalline ball milled Cu-Zr samples heat treated to either have only ordered grain boundaries or to contain AIFs distributed within the grain boundary network.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology has been advancing steadily in the past several decades. Manufactured at the nanoscale level, some nanomaterials have achieved the dual properties of high strength and ductility [18], while others have unique electrical, magnetic, optical, and chemical properties. In some cases, anisotropic behavior for the above properties is observed in nanoparticles and materials.…”
Section: Delicate and Difficult Materialsmentioning
confidence: 99%